Rituximab in childhood steroid-sensitive nephrotic syndrome: are multiple subsequent courses safe and effective?. Issue 8 (11th November 2020) - Subun, Chantida; Suwannahitatorn, Picha; Webb, Hazel; Tullus, Kjell
Abstract : Introduction: Idiopathic nephrotic syndrome is the most common glomerular disease in children. The majority of patients respond well to steroids. However, the relapse rate is high and many develop steroid dependency. Although other immunosuppressive medicines are successfully used as steroid-sparing agents, some children still have frequent relapsing episodes. Rituximab (RTX), a chimeric anti-CD20 monoclonal antibody, has shown to be effective in treating difficult frequently relapsing/steroid-dependent nephrotic syndrome (FR/SDNS). Data on the effectiveness and long-term treatment outcomes of repeated courses of RTX are, however, scarce. Material and methods: Children and young people with FR/SDNS, aged 1–18 years, who received RTX at Great Ormond Street Hospital (GOSH) from 2006 to 2018 were reviewed. Results: During these 12 years, 103 children with FR/SDNS received RTX infusions at GOSH. Among these, 58 cases needed repeated courses of RTX: 2, 3, 4, 5, 6 and 7 repeated courses were given to 21, 21, 7, 5, 1 and 3 patients, respectively. The overall median time to relapse post-RTX was 11 months (range 1–53 months). There was no change in relapse-free interval with subsequent courses of RTX. No difference was found between age groups, genders and ethnicities. No severe side effects were noted. Conclusions: RTX seems to be safe even after several repeated courses. However, long-term follow-up and further studies are needed, with a focus on side-effects in particular.